SPIRITUALITAS POLITIK SEBAGAI DASAR PERJUANGAN MASYARAKAT ADAT SAMIN MELAWAN EKONOMI KAPITALISME PABRIK SEMEN DI PEGUNUNGAN KENDENG, SUKOLILO PATI - Johan Christian Filipus (SAGACITY : Journal of Theology and Christian Education, 2023)
Abstract: This article aims to describe the social movement of the Samin indigenous people in fighting for environmental justice against the cement factory in the Kendeng mountains as the face of the representation of capitalism. The social movement pioneered by the Samin indigenous people is very unique because this struggle is accompanied by the use of symbols of local cultural traditions of the Samin indigenous people. This article will use the eco-feminist conception as a political movement to analyze the social structure that perpetuates the practice of capitalism and the conception of the spiritual paradigm of the indigenous people as an analysis of the local epistemology of the Samin indigenous people in laying down the ethical awareness of the preservation of the Kendeng mountain nature conservation movement. These two analyzes become the construction knowledge of the local Samin indigenous people in planning action against the expansion of capitalism in the cement factory industry in the Kendeng mountains, Sukolilo, Pati district. The movement pioneered by the Samin indigenous people can be a trigger for environmental ethics discourse and a trigger for public policy makers in presenting political-economic decisions that can give ethical considerations to environmental sustainability